MATHEMATICAL CRITICAL THINKING ABILITY THROUGH CONTEXTUAL TEACHING AND LEARNING APPROACH - Kurniati Kurniati; Yaya S. Kusumah; Jozua Sabandar; Tatang Herman (Journal on Mathematics Education, 2015)
This research aimed to examine the effect of the application of contextual teaching and learning (CTL) approach to the enhance of mathematical critical thinking ability (MCTA) of Primary School Teacher Students (PSTS). This research is an experimental study with the population of all students PSTS who took algebra subject matter of one  university in the city of Bogor. The results showed: (1) the increase of MCTA of student who receive CTL better than students who receive TTL; (2) There are differences in the increase MCTA between students in groups of high MPA, medium MPA, and low MPA, both the student who received the CTL and TTL; and (3) There is no interaction between learning factors (CTL and TTL) with MPA (high, medium and low) toward the enhance of MCTA.Keywords: Critical Thinking Ability in Mathematics, Contextual Teaching and Learning Approach, Prior Mathematical Ability DOI: dx.doi.org/10.22342/jme.61.53